Democracy, Threat Reconfiguration, and South American Peace - Jorge Battaglino (Íconos)
This paper claims that South American democracies have demonstrated a notable predisposition toward bilateral agreements, toward the search for arbitration/mediation, and toward the establishment of inter-democratic regional institutions. These traits have favored the resolution of the majority of regional conflicts, or if not resolution, then conflict management through different institutions. Likewise, the proliferation and consolidation of regional peace has precipitated a phenomenon of democratic peace that went unanticipated by the literature: the reconfiguration of threats, which, through its own momentum, reinforces South American peace.